2014
DOI: 10.1371/journal.pone.0084312
|View full text |Cite|
|
Sign up to set email alerts
|

Texting and Walking: Strategies for Postural Control and Implications for Safety

Abstract: There are concerns about the safety of texting while walking. Although evidence of negative effects of mobile phone use on gait is scarce, cognitive distraction, altered mechanical demands, and the reduced visual field associated with texting are likely to have an impact. In 26 healthy individuals we examined the effect of mobile phone use on gait. Individuals walked at a comfortable pace in a straight line over a distance of ∼8.5 m while; 1) walking without the use of a phone, 2) reading text on a mobile phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
141
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(162 citation statements)
references
References 25 publications
17
141
1
3
Order By: Relevance
“…Seventy-seven percent of the world's population have mobile phones, and they have been recognized as a cost-effective communication tool [1]. Although mobile phones provide great convenience, they cause risks in certain situations [2].…”
Section: Introductionmentioning
confidence: 99%
“…Seventy-seven percent of the world's population have mobile phones, and they have been recognized as a cost-effective communication tool [1]. Although mobile phones provide great convenience, they cause risks in certain situations [2].…”
Section: Introductionmentioning
confidence: 99%
“…When fixing gaze on a mobile phone, visual information regarding the walking environment is reduced [33]. Schabrun et al [2] reported that, to minimize neck movement during mobile phone use while walking, neck range of motion and gait speed reduced. Decreased gait speed could be caused by a decreased arm swing [34].…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-seven percent of the world's population use personal mobile phones as a communication tool and texting and transmission of data using mobile phones has been sharply increasing [1,2]. Increased mobile phone use has initiated many safety-related issues [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the study, complex interference effects, such as breathing in the spontaneous speech condition, also helped people synchronize their pace. Schabrun, van den Hoorn, Moorcroft, Greenland, and Hodges (2014) found that using a smartphone display, for example, typing or reading a text message while being in motion, affects the user's gait and balance drastically. Their participants' gait changed when using their mobile phone, with sending a text having a bigger impact than simply reading one.…”
Section: Rhythm Synchrony and Balancementioning
confidence: 99%